Análise da ligação RAGE/HMGB1 no volume ósseo do reparo ósseo alveolar em camundongos - Borges, Thainan de Santana (2018)
The bone repair development and neoformation processes are essential for tissue homeostasis after trauma or bone loss. Thus, modulation of immune / inflammatory response is a strategy to understand and improve this process. Interesting possibilities emerging to correlate immune system and bone system, after the discovery of inflammatory signaling mediated by the RAGE receptor and the HMGB1 ligand. In this way, this study aimed to elucidate the influence of the RAGE / HMGB1 complex in the immune / inflammatory response after exodontia of the upper incisor of C57Bl/7 mice.40 mice were divided into two groups [Control Group - WT; Group GLY - treated with glycyrrhizin (HMGB1 inhibitor)] and analyzed in 0, 7, 14, 21 days after exodontia. Histomorphometric analysis showed a very similar kinetics between WT and GLY groups in relation to the bone matrix. GLY group presented a lower density in the osteoblast volume and higher amount of osteoclast compared to control group at 7 and 14 days (p <0.05). Similarly, to volume density of osteoblasts, GLY presented lower bone density at day 21, and this density was higher when compared to WT mice. Therefore, inhibition of HMGB1 was not able to interfere with the kinetics of alveolar bone repair in mice, however showed differences in some components involved in the kinetics of alveolar bone repair.